PENGARUH PENGGUNAAN MODEL GENERATIVE LEARNING TERHADAP PEMAHAMAN KONSEP DAN PENALARAN MATEMATIKA PESERTA DIDIK KELAS VIII SMP 14 BENGKULU TENGAH - Fashali, Agju Jihan Indri; Susanta, Agus; Haji, Saleh (LPPM Universitas Bina Bangsa, 2024)
The capacity to comprehend concepts and reasoning in students when addressing mathematical problems is notably low, resulting in a significant number of students who struggle to independently tackle practice problems.This study aims to examine 1) the effect of the Generative Learning Model on the conceptual understanding abilities of eighth-grade students at SMPN 14 Bengkulu Tengah, 2) the effect of the Generative Learning Model on the mathematical reasoning abilities of eighth-grade students at SMPN 14 Bengkulu Tengah, and 3) the effect of the Generative Learning Model on both the conceptual understanding and mathematical reasoning abilities of eighth-grade students at SMPN 14 Bengkulu Tengah. The sampling technique employed is nonprobability sampling, specifically utilizing saturated sampling (census). The data analysis method applied in this study is the MANOVA technique. The findings indicate that 1) the Generative Learning Model significantly influences the conceptual understanding abilities of eighth-grade students at SMPN 14 Bengkulu Tengah, with a significance value of > 0.05, 2) the Generative Learning Model significantly influences the mathematical reasoning abilities of eighth-grade students at SMPN 14 Bengkulu Tengah, with a significance value of > 0.05, and 3) the Generative Learning Model significantly influences both the conceptual understanding and mathematical reasoning abilities of eighth-grade students at SMPN 14 Bengkulu Tengah, with a significance value of > 0.05